Prometheus bound? European initiatives and trends on Higher Education and their association with economic competiveness, skills and employability. - Papadakis, Nikos Eystathios; Drakaki, Maria (Advances in Social Sciences Research Journal, 2021)
Globalization and increasing internationalization of Higher Education has clearly resulted in a persistent demand for the further transformation of Higher Education Institutes (HEIs), towards competitiveness and contribution to development. What is actually in stake is the employability, while another key issue is the harmonization with the economy and the labor market. That raises, of course, a lot of issues concerning the gradual transformation of the Higher Education and the relation between Higher Education and Society at Large. Globalization has affected all the abovementioned, which is crystal clear in large scale initiatives, in Europe, such as the “Bologna Process” and the subsequent development of the European Higher Education Area, in the case of Europe. Given all the abovementioned, the present article mainly focuses on the European trends, transformations and initiatives in Higher Education, related to HEIs’ active and potential contribution to economic development and the enhancement of graduates’ employability and skills.